NECTIN4 amplification as a predictive biomarker for enfortumab vedotin response NECTIN4-Amplifikation als prädiktiver Biomarker für das Ansprechen auf Enfortumab-Vedotin - Eckstein, Markus (Die Pathologie, 2025)
Enfortumab vedotin (EV) is a targeted antibody-drug conjugate (ADC) directed against NECTIN4 and approved for treatment of metastatic urothelial carcinoma (mUC) after failure of platinum-based chemotherapy and immune checkpoint inhibitors. However, not all patients benefit equally from EV, highlighting the need for a predictive biomarker. In this multicenter study, 108 EV-treated mUC patients were analyzed for genomic NECTIN4 amplifications using fluorescence in situ hybridization (FISH). Approximately one-quarter of tumors showed NECTIN4 amplification, which was strongly associated with increased membranous protein expression and an objective response rate of 96%. Amplified tumors also had significantly prolonged overall survival. In a control cohort without EV, NECTIN4 amplification had no prognostic impact. These findings identify NECTIN4 amplification as a stable, predictive biomarker that may guide treatment decisions in mUC. Data from TCGA further suggest a cross-entity relevance of NECTIN4 amplification, supporting future clinical exploration of EV in other solid tumors.
CRIS-Team Scopus Importer:2025-11-28
Keywords: Antibody-drug conjugate; Biomarker; Enfortumab vedotin; NECTIN4; Urothelial carcinoma